2014
DOI: 10.1016/j.eja.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green manure herbage management and its digestate from biogas production on barley yield, N recovery, soil structure and earthworm populations

Abstract: 30In repeatedly mown and mulched green manure leys, the mulched herbage contains substantial amounts of 31 nitrogen (N), which may only slightly contribute to the following crops´ nutrient demand. The objective of the 32 present work was to evaluate the effect of alternative strategies for green manure management on the yield and N 33 recovery of a subsequent spring barley crop, and their short term effects on soil structure and earthworm 34 populations. A field trial was run from 2008 to 2011 at four sites wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 46 publications
4
57
0
3
Order By: Relevance
“…Our results are consistent with those reported by others for digestates (Terhoeven-Urselmans et al, 2009;Garfí et al, 2011;Barbosa et al, 2014;Bachmann et al, 2014;Frøseth et al, 2014) and for CM and SS (Chiyoka et al, 2014). In addition, the higher forage yields in response to ADM than CM and SS application reflected greater available N and P concentrations in ADM (Table 3), in agreement with results reported by others (Tambone et al, 2010).…”
Section: Barley Forage Responsesupporting
confidence: 83%
“…Our results are consistent with those reported by others for digestates (Terhoeven-Urselmans et al, 2009;Garfí et al, 2011;Barbosa et al, 2014;Bachmann et al, 2014;Frøseth et al, 2014) and for CM and SS (Chiyoka et al, 2014). In addition, the higher forage yields in response to ADM than CM and SS application reflected greater available N and P concentrations in ADM (Table 3), in agreement with results reported by others (Tambone et al, 2010).…”
Section: Barley Forage Responsesupporting
confidence: 83%
“…For example, there are some indications in a number of trials that earthworm populations react differently to slurry or digestate applications, with Lumbricus terrestris preferring slurry and Eisenia fetida preferring digestate (Clements 2013). Another study indicates that digestates did not influence earthworm populations, whereas earthworms were positively influenced by the green manure crop otherwise used as feedstock for anaerobic digestion (Frøseth et al 2014). Alburquerque et al (2012b) found a significant increase in alkaline phosphatase activity (linked to the P cycle) in soils treated with digestates; however, no changes in β-glucosidase (linked to the carbon cycle), urease, and protease (both linked to the N cycle) activities were measured.…”
Section: Effects Of Anaerobic Digestion On Soil Properties and Soil Bmentioning
confidence: 99%
“…Application of digestates improved soil properties by reducing the bulk density, increasing saturated hydraulic conductivity, moisture retention capacity of soils (Garg et al 2005;Beni et al 2012), and aggregate stability (Beck and Brandhuber 2012;Beni et al 2012;Erhart et al 2014;Frøseth et al 2014), compared to an untreated control. However, an assessment on the long-term direct effects of digestate application on soil physical properties in comparison to the undigested feedstock is not available.…”
Section: Effects Of Anaerobic Digestion On Soil Properties and Soil Bmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, there will be a trend to integrate green manure in agricultural system as an alternative strategy for lowering chemical fertilizer usage and restoring a deteriorated field environment. Current research focuses on improving soil physical and biochemical properties [1][2][3][4][5][6][7][8][9][10][11][12][13][14], contaminated soil rehabilitation [15][16][17][18][19][20][21][22], improving crop yield [13,[23][24][25][26], development of sustainable agricultural system [27][28][29][30][31][32] at the micro scale. However, developing green manure at a regional scale is especially affected by both human interventions and the natural soil properties.…”
Section: Introductionmentioning
confidence: 99%